Analisis Strategi CBT: Pelaksanaanya dalam Konseling - Abdilah, Aida; Yulistina, Ina; Mutamimah, Mutamimah (Universitas Mathla'ul Anwar Banten, 2025)
This study aims to examine the implementation of Cognitive Behavioral Therapy (CBT) strategies in counseling services through a literature study method. Data were collected from literature published in the period 2019–2024 and obtained through a systematic search on Google Scholar, with selection based on relevance, scientific feasibility, and topic recency. Analysis of 15 primary studies showed that CBT has been proven effective in individual and group counseling to deal with various psychological problems, such as social anxiety, obsessive compulsive disorder (OCD), low self-esteem, self-esteem, self-efficacy, learning difficulties, deviant behavior, and smartphone addiction. Various CBT techniques used include cognitive restructuring, self-management, modeling, role playing, and integration with other interventions such as music therapy and Islamic counseling. The dominant research designs are pre-experimental experiments, quasi-experimental experiments, and single subject designs with relevant psychological instruments and statistical analysis. The results of the study show that the implementation of CBT in counseling can change negative thought patterns to positive ones, improve emotional regulation, and significantly improve client behavior. These findings confirm that CBT is an effective and adaptive strategy to be implemented in various counseling services in Indonesia.